Terrestrial Maternity Denning of Polar Bears in the Eastern Beaufort Sea Area - Stirling, Ian; Andriashek, Dennis (ARCTIC, 1992)
Observations on the location of polar bear (Ursus maritimus) maternity dens, the locations of females with young cubs on the sea ice just after leaving their dens, and observations of Inuvialuit hunters were recorded in the eastern Beaufort Sea area from late March to mid-May 1971-79 and 1985-87. Maternity denning occurs annually on the west and south coasts of Banks Island but it has been recorded less frequently along the mainland coast of the southern Beaufort Sea. This distribution pattern could have been influenced by the pattern of sea ice formation in the fall and anthropogenic factors. Denning females and females accompanied by young cubs have been protected for almost 20 years, and maternity denning along the mainland coast appears to be increasing as a result.Key words: polar bear, denning, Beaufort Sea, Banks Island RÉSUMÉ. Des observations faites sur l’emplacement des tanières de mise bas d’ourses polaires (Ursus maritimus), l’emplacement des femelles avec leurs oursons sur la banquise juste après l’abandon de la tanière ainsi que des observations faites par des chasseurs Inuvialuit ont été enregistrées dans la mer de Beaufort de la fin mars à la mi-mai de 1971à 1979 et de 1985 à 1987. La mise bas dans les tanières à eu lieu chaque année sur la côte occidentale et méridionale de l’île Banks mais on l’a rapportée moins fréquemment le long du rivage continental du sud de la mer de Beaufort. Il se peut que ce schéma de distribution ait été influencé par le schéma de formation de la banquise à l’automne et par des facteurs anthropiques. Les femelles qui mettent bas et celles accompagnées de leur oursons sont protégées depuis au moins 20 ans, ce qui semblerait résulter en une augmentation de la mise bas dans des tanières le long du rivage continental.Mots clés: ours polaire, tanière de mise bas, mer de Beaufort, île Banks